Effect of Landscape Positions on Soil Properties in an Agricultural Land A Transect Study in the Main Rift Valley Area of Ethiopia - Yimer, Fantaw (Journal of Science and Development, 2017)
This study addressed the effects of landscape positions on morphological, physicochemical properties of soils inthe Main Rift Valley of Ethiopia. Three landscape positions: upper, middle and lower; and three profile horizons:A, B and buried Ab were considered along a transect line. Nine soil profiles; three in each landscape position,were opened, described and samples collected from each of the observed diagnostic horizon and analyzed. Theaverage thickness of the A- horizon was 34 cm in the upper, 10 cm in the middle and 50 cm in the lower landscapepositions. Gravels and high sand fractions (average, 41.4%) dominated the B-horizons, indicating the low rate ofweathering. The clay fractions and soil bulk density (p<0.001), available water capacity (AWC) (p=0.050), soilorganic carbon (SOC) and total N (p= 0.004 and 0.025, respectively), Available P (p=0.004), Exchangeable Ca2+(p=0.019) and CEC (p=0.010) varied significantly with horizons. Landscape positions also influenced the texturalfractions of clay, bulk density, AWC, SOC, total N, available P, exchangeable Ca2+ and CEC. However, the SOCconcentration across the profiles were low due to the combination of lower inputs because of less biomass returnon harvested land, increased aeration by tillage and crop residue collection for fire. The low available P might bedue to the high P-fixation behavior of andosols. Continuous cultivation without appropriate soil managementpractices has resulted in more complex and non-systematic patterns of soil nutrient distribution. Thus, landscapelevel management practices are required to replenish soil nutrients for sustainable agriculture.